SISTEM INFORMASI EKSEKUTIF PENGIRIMAN SMS PADA PT INDOSAT SEMARANG BERBASIS WEB (Information Technology and Telematics, 2013)
PT. INDOSAT Tbk is one of the biggest telecommunications company in Indonesia. Indosat providing cellular services includes telephonies services,short message services and data services. Short Message Services ( SMS ) is one of the services which is allow the user to exchange text between them. As one of the main services from the INDOSAT,we need to maintain and check regularly of the SMS delivery systemat the Mobile Switching Center ( MSC ) to keep it at it’s best. The system that we know now is still doing the maintenance manually. It’s take too much time and that’s make it not the most effective way to do the maintenance. The main purpose of this program is to replace the manual system for making the SMS delivery system report that using microsoft excel with automatic SMS delivery system report by web. The input of this program  is from the raw data ( microsoft excel ) and the output is the chart. The output is used by manager to assist in the decision making process.  Keywords :SMS delivery system, grafik batang, Sistem Informasi, web based, MSC.